2019
DOI: 10.1002/chem.201805409
|View full text |Cite
|
Sign up to set email alerts
|

A Click‐Chemistry Linked 2′3′‐cGAMP Analogue

Abstract: 2′3′‐cGAMP is an uncanonical cyclic dinucleotide where one A and one G base are connected via a 3′‐5′ and a unique 2′‐5′ linkage. The molecule is produced by the cyclase cGAS in response to cytosolic DNA binding. cGAMP activates STING and hence one of the most powerful pathways of innate immunity. cGAMP analogues with uncharged linkages that feature better cellular penetrability are currently highly desired. Here, the synthesis of a cGAMP analogue with one amide and one triazole linkage is reported. The molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…To which extent the synthesis can be transferred to a larger scale cannot be estimated from the data published to date. Another recently published synthesis route based on click chemistry reactions resulted in a 2′3′‐cGAMP analog with neutral linkages that is characterized by a better cell membrane penetrability (Dialer et al, 2019). The labile and charged phosphate groups were replaced by an amide bond and a triazole linkage.…”
Section: Current Chemical and Biocatalytic Synthesis Routesmentioning
confidence: 99%
See 1 more Smart Citation
“…To which extent the synthesis can be transferred to a larger scale cannot be estimated from the data published to date. Another recently published synthesis route based on click chemistry reactions resulted in a 2′3′‐cGAMP analog with neutral linkages that is characterized by a better cell membrane penetrability (Dialer et al, 2019). The labile and charged phosphate groups were replaced by an amide bond and a triazole linkage.…”
Section: Current Chemical and Biocatalytic Synthesis Routesmentioning
confidence: 99%
“…The 20‐step synthesis of this uncharged product resulted in a yield of 1%. Unfortunately, the product lacked affinity towards the STING receptor (Dialer et al, 2019). Beside the solution‐phase synthesis, solid‐phase synthesis of c‐di‐GMP starting from 3′‐phosphate controlled pore glass as carrier material was demonstrated (Kiburu et al, 2008).…”
Section: Current Chemical and Biocatalytic Synthesis Routesmentioning
confidence: 99%
“…The synthesis of cyclic dinucleotides with nonphosphate linkages is also beyond the scope of enzymatic synthesis. [127] Chemical synthesis provides an alternative approach for the preparation of 2',3'-cGAMP analogues and has complementary advantages with enzymatic synthesis. Chemical synthesis of cyclic dinucleotides can be traced back to the 1950s when Khorana tried to synthesize oligonucleotides based on the phosphodiester method.…”
Section: Chemical Synthesismentioning
confidence: 99%
“…[153][154][155] Recently, Carell reported the synthesis of 2',3'-cGAMP analogues with one amide and one trizole linkage (Scheme 10B). [127] The trizole linkage between the C3' of adenosine and C5' of guanosine is first constructed based on Cu(I)-catalysed click chemistry. Then, the obtained dinucleotide is subjected to cyclization based on the coupling of the 5'-NH 2 of adenosine with the 2'-acetic acid of guanosine.…”
Section: Synthesis Of Neutral 2'3'-cgamp Analoguesmentioning
confidence: 99%
“…Most of the currently reported CDN derivatives are limited to those with a phosphodiester skeleton, which are prone to degradation by PDE [ 48 , 49 , 50 , 51 , 52 , 53 ]. Although several research groups have reported CDN derivatives where the phosphodiester-sugar backbone is replaced with a different linker structure [ 54 , 55 , 56 ], there are no examples of CDN-based STING ligands with substitution of the entire sugar-phosphodiester backbone. In this study, we designed new CDN mimetics with the phosphodiester skeleton replaced by an amine skeleton, which is easy to synthesize and derivatize.…”
Section: Introductionmentioning
confidence: 99%